2019
DOI: 10.3390/ijerph16091658
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Features of Parks That Children Visit During Three Stages of Childhood

Abstract: Parks provide an opportunity for children to be physically active, but are rarely fully utilised. A better understanding of which park features attract children of varying ages is needed. This study examined which features are present at parks that children visit most often at different stages throughout childhood. Parents reported the park their child visited most often at three timepoints: T1 = 3–5 years, T2 = 6–8 years, and T3 = 9–11 years. These parks were then audited (using a purposely created audit tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 28 publications
(38 reference statements)
0
22
0
1
Order By: Relevance
“…Given that park satisfaction may be related to park quality in terms of amenities, maintenance and aesthetics [ 24 ] this finding is contrary to those from previous studies among adults and adolescents that suggest quality of parks is more important than quantity or availability for encouraging park use [ 27 , 30 , 43 ]. Inconsistencies amongst children’s park satisfaction may also be explained by subtle differences in park use and park feature requirement at different ages throughout childhood [ 26 ]. Future studies are required to better understand the qualities and features of parks that contribute to overall park satisfaction for different user groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that park satisfaction may be related to park quality in terms of amenities, maintenance and aesthetics [ 24 ] this finding is contrary to those from previous studies among adults and adolescents that suggest quality of parks is more important than quantity or availability for encouraging park use [ 27 , 30 , 43 ]. Inconsistencies amongst children’s park satisfaction may also be explained by subtle differences in park use and park feature requirement at different ages throughout childhood [ 26 ]. Future studies are required to better understand the qualities and features of parks that contribute to overall park satisfaction for different user groups.…”
Section: Discussionmentioning
confidence: 99%
“…We know that people do not always visit their closest park and often travel significant distances from home to reach their preferred park [ 25 , 26 ]. This may be due to (dis) satisfaction with the features or quality (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…According to the opinion of family members and caregivers of children from 0 to 6 years old, to encourage greater use of these spaces, playgrounds should offer opportunities for outdoor activities with green areas and forests [ 60 , 65 , 83 ], and be close to their residence or where their friends or relatives live (60,65,81], as this will allow them to interact with other children or with their parents. Parks should allow the performance of various activities and games that motivate children [ 60 , 69 ], with safety and cleanliness being another factor that encourages visits [ 65 , 83 ]. However, family members and caregivers aged 7 to 12 choose large parks (even if they are not located near their residential area) [ 60 ] and, with sports facilities and other amenities such as bathrooms, seats, fountains with drinking water, barbecues and gardens [ 49 , 57 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parks should allow the performance of various activities and games that motivate children [ 60 , 69 ], with safety and cleanliness being another factor that encourages visits [ 65 , 83 ]. However, family members and caregivers aged 7 to 12 choose large parks (even if they are not located near their residential area) [ 60 ] and, with sports facilities and other amenities such as bathrooms, seats, fountains with drinking water, barbecues and gardens [ 49 , 57 , 78 ]. In addition, they must have areas that allow different age groups to exercise (multigenerational parks) [ 64 ], have different play areas [ 78 ], that are accessible [ 51 , 64 , 78 ], of high quality [ 83 ] and restrictions on dogs, vandalism, litter and fencing.…”
Section: Discussionmentioning
confidence: 99%
“…Observational and activity tracking studies show that children engage in a variety of activities at parks such as playing and exploring [ 24 ], and these activities and park needs vary even throughout childhood. For example, a recent study exploring differences in features present in parks visited by children of different ages (3–5, 6–8, 9–11 years), found that older children (9–11 years) were more likely to visit larger parks that had more facilities and were further away from home compared with younger children [ 25 ]. It is therefore critical to ensure that evidence-based park design considers all demographic groups.…”
Section: Introductionmentioning
confidence: 99%